INTERNATIONALIZATION OF HIGHER EDUCATION AT THE UNIVERSITY OF ECONOMICS: MODELS, TECHNOLOGIES, AND PROSPECTS FOR DEVELOPMENT - Lyudmila A. Barahtenova (Высшее образование в России)
The fundamentals of the methodology of the internationalization of higher education is presented, as well as the model structure of the concept «internationalization of education».Taking the example of the Novosibirsk State University of Economics and Management the paper shows the features of the design and development of a model of international education that allows to implement a variety of innovative educational technologies (franchising, dual diplomas, etc.). The prospects for the model as a tool for the formation of professional networks of the NSUEM with foreign partner universities are demonstrated.